EQUITY IN INDIA: COMPARISON WITH COMMON LAW - Anwesha Tripathy , Maithili Chaudhury (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The equity system involves the natural justice principle, which is constitutionally constitutional, but for many reasons has not been applied by common law courts'1.' EQUITY is that legal framework where, in the operation of both the extraordinary sovereignty, has been established and implemented in England by the constitutional court of Chancelloring. This description is more descriptive than accurate; rather than responses, it invites investigation. EQUITY means neither equality and justice nor well all the pieces of due process that can be judiciarily applied in their technological and scientific legal context.This article follow the history and advancement of value and furthermore it analyses the significance which is essential for Indian Legitimate framework. They often try to specifically clarify and determine the reasons why the previous law courts are frustrated in the achievement of social reform, and encourage strategies to address obstacles. Shift of development of a person to common law, what led to the law of value being created, in which lord supports matters in cases where the offended party isn't really pleased with their choice. This article focuses on the source, development and its consequences and importance in the legally binding Indian context.In India, too certain statutes such as the transfer of property legislation have been extracted and have had a major impact on the functioning of a legal Indian system.